Threshold effects of influencing factors on green efficiency of water resources based on environmental regulation and resource endowment: A case study of Heilongjiang Province, China - Yunxing Wu; Yiting Zhang; Ruirui Long; Zilong Wang; Qiuxiang Jiang (Ecological Indicators)
The core of green efficiency of water resources (GEWR) improvement is to achieve water efficiency growth based on environmental improvement and resource conservation. To explore the influence of environmental regulation (ER) and resource endowment (RE) on the GEWR, in this paper, the slacks-based measure (SBM) model was used to measure the GEWR in 13 regions in Heilongjiang Province, China. The linear relationship between the GEWR and influencing factors was determined by establishing a panel baseline regression model, and the threshold regression model was used to study the threshold effects of ER and RE. The results showed that: (1) The GEWR in Heilongjiang Province exhibited a fluctuating upward trend from 2003 to 2018 and that of most regions was below 0.5. (2) There is a significant threshold relationship between ER and RE and GEWR. For ER of > 0.727, ER changed from positive to negative impact on GEWR; For RE of > 6.616, the negative impact of RE on GEWR was enhanced, and for RE of > 6.674, the impact of ER on GEWR changed from positive to negative. (3) Economically developed areas, such as Daqing and Harbin, tend to have higher ER; while regions with favorable water resource conditions, such as Mudanjiang and Jixi, exhibit RE above the threshold (6.674). This paper provides theoretical support for the implementation of differentiated ER policies in different REs, and recommendations for efficient water resource utilization in the actual situation are suggested.